Modelling and analysing deadlock in flexible manufacturing system using untimed petri net - Al Hazza, Muataz Hazza Faizi; Taha, Assem Hatem; Adesta, Erry Yulian Triblas; Albakri, Adilah (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Manufacturing systems nowadays become more complex due to the need for more flexibility. One of the main problems that may happen due to the flexibility is the deadlock due to many reasons. Sharing resources is one of these reasons.Deadlock is a case that happens when an operation are not able to finish the job because of waiting of these shared resources that are used by other processes. To avoid these phenomena, a modelling and simulating for the lexible system using one of the modelling approaches will help to avoid the deadlock. One of the most effective tools to model and detect the deadlocks is the untimed petri net. In this research the Matlab software has been used to detect the deadlock in two parallel lines with one shared machines. The analysis shows that deadlock exists at transition with high utilization and place with high waiting time